(untitled) (SAARC Journal of Agriculture, 2021)
This study was aimed to investigate the socio-economic characteristics and present scenario of farmers engaged in sheep production at Sherpur district in Bangladesh. Data were primarily collected with a pre-tested interview schedule from the local sheep farmers. Results showed that average family size, male and female ratio and age was 5.58, 3:10, and 45.23 year, respectively. Family size, land size and yearly livestock income was found significant (P<0.01). Most of the farmers belong to primary education (46.70%) and illiterate (30.00%). Maximum numbers of farmers belong to small holder (81.91 decimal of land). The average monthly income and expenditure of farmers was estimated BDT 10123.00 and 11476.00, respectively. The male partner was dominant over female partner in different decision-making process. The co-efficient of family size (-9843.99), land size (404.27) and yearly livestock income (1.02) was significantly different (P<0.05). It is implied that one unit increases of land size and yearly livestock income might help in increasing 404.27 and 1.02 unit in family yearly income, respectively whereas, one unit increase of family size, resulted 9843.99 unit decreases of yearly family income, considering all other variables constant. It is concluded that there is great opportunity to improve livelihood of the small farmers particularly increase family income through sheep farming in the study areas. SAARC J. Agric., 19(1): 185-199 (2021)